Divergent Capacity of Scleractinian and Soft Corals to Assimilate and Transfer Diazotrophically Derived Nitrogen to the Reef Environment - Pupier, Chloé A.; Bednarz, Vanessa N.; Grover, Renaud; Fine, Maoz; Maguer, Jean-François; Ferrier-Pagès, Christine (Frontiers in Microbiology, 2019)
Corals are associated with dinitrogen (N2)-fixing bacteria that potentially represent an additional nitrogen (N) source for the coral holobiont in oligotrophic reef environments. Nevertheless, the few studies investigating the assimilation of diazotrophically-derived nitrogen (DDN) by tropical corals are limited to a single scleractinian species (i.e. Stylophora pistillata). The present study quantified DDN assimilation rates in four scleractinian and three soft coral species from the shallow waters of the oligotrophic Northern Red Sea using the 15N2 tracer technique. All scleractinian species significantly stimulated N2 fixation in the coral-surrounding seawater (and mucus) and assimilated DDN into their tissue. Interestingly, N2 fixation was not detected in the tissue and surrounding seawater of soft corals, despite the fact that soft corals were able to take up DDN from a culture of free-living diazotrophs. Soft coral mucus likely represents an unfavorable habitat for the colonization and activity of diazotrophs as it contains a low amount of particulate organic matter, with a relatively high N content, compared to the mucus of scleractinian corals. In addition, it is known to present antimicrobial properties. Overall, this study suggests that DDN assimilation into coral tissues depends on the presence of active diazotrophs in the coral’s mucus layer and/or surrounding seawater. Since N is often a limiting nutrient for primary productivity in oligotrophic reef waters, the divergent capacity of scleractinian and soft corals to promote N2 fixation may have implications for N availability and reef biogeochemistry in scleractinian versus soft coral dominated reefs.